Taxes and Subsidies in Leontief's Input-Output Model - Metzler, Lloyd A. (Quarterly Journal of Economics, 1951)
Journal Article Taxes and Subsidies in Leontief's Input-Output Model Get access Lloyd A. Metzler Lloyd A. Metzler University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 65, Issue 3, August 1951, Pages 433–438, https://doi.org/10.2307/1882224 Published: 01 August 1951